Eliminación del Plazo de Transferencia establecido en el artículo 30 de la Ley de Minería - Cuenca Solano, Kevin Daniel (2020)
The present research presented under the Thesis modality refers to a legal problem that deserves to be transformed to solve and overcome the socio-legal problem identified in Article 30 of the Mining Law in its third paragraph stipulates “Authorize the transfer of the mining title at least after two years of its granting ”, since this is a time that could generate, damages of the economic rights, and investments of the mining concessionaire, the practice of assignments and transfers of mining concessions; having a deadline is a limitation on the Rights, not only of the concessionaires and their families, but also that limits mining production and development, since two years must be waited to cease and transfer the Mining Rights. Therefore, it is necessary to reform the ibid rule by eliminating the transfer period of two years, in order to eliminate the limitation of dealers and their families. All this has been reflected in the proposal for legal reform that is at the end of the present investigation and that I put to the consideration of the National University of Loja, and of all those who have some affinity with the problematic matter of this research work.